(untitled) (Economic and Political Thought, 2023)
The aim of the article is to analyze the importance of Pakistan, as one of the influential countries of the Indo-Pacific region, for the broadly understood security of China during the rule of Xi Jinping in the context of the American strategy in the region. Pakistan is undoubtedly one of the participants in the competition between the US and China. Its geographical location is of geostrategic and geoeconomic importance for Beijing. Pakistan plays an important role in the process of redefining China’s security interests in the Indo-Pacific region and increases its power projection capabilities. Beijing’s relations with Islamabad are filled with new content, especially in the context of formulating the American concept of regional security, which has a clearly anti-Chinese character. The US system of alliance ties in the Indo-Pacific region is based on countries whose relations with China are tense and historically burdened. India ranks first among these countries. In this context, Pakistan serves as an ally to China that expands its room for maneuver in the process of balancing relations in the region.